Various myosteatosis selection criteria and their value in the assessment of short- and long-term outcomes following liver transplantation - Franziska Alexandra Meister (Nature Portfolio, 2021)
Abstract Body composition and myosteatosis affect clinical outcomes in orthotopic liver transplantation (OLT). Here we aimed to compare the value and limitations of various selection criteria to define pre-transplant myosteatosis in the assessment of short- and long-term outcomes following OLT. We retrospectively analyzed the data of 264 consecutive recipients who underwent deceased donor OLT at a German university medical centre. Myosteatosis was evaluated by preoperative computed-tomography-based segmentation. Patients were stratified using muscle radiation attenuation of the whole muscle area (L3Muslce-RA), psoas RA (L3Psoas-RA) and intramuscular adipose tissue content (IMAC) values. L3Muslce-RA, L3Psoas-RA and IMAC performed well without major differences and identified patients at risk for inferior outcomes in the group analysis. Quartile-based analyses, receiver operating characteristic curve and correlation analyses showed a superior association of L3Muslce-RA with perioperative outcomes when compared to L3Psoas-RA and L3IMAC. Long-term outcome did not show any major differences between the used selection criteria. This study confirms the prognostic role of myosteatosis in OLT with a particularly strong value in the perioperative phase. Although, based on our data, L3Muscle-RA might be the most suitable and recommended selection criterion to assess CT-based myosteatosis when compared to L3Psoas-RA and L3IMAC, further studies are warranted to validate these findings.